Efficiency of Microfinance Institutions in India: A Two-Stage DEA Approach. (April 2019) - Sinha, Ram Pratap; Pandey, Pallavi
The present study uses robust data envelopment analysis to estimate the performance of 30 Indian microfinance institutions (MFIs) from 2008–2009 to 2015–2016. Due to the non-availability of information in some instances, the present study uses an unbalanced panel of observations. In the matter of evaluation of performance, the study makes a major departure from the extant studies undertaken in the Indian context and adopts a double bootstrap approach originally suggested by Simar and Wilson. The current approach thus evaluates conditional performance of the in-sample MFIs in the presence of capital-to-asset ratio as an environmental variable. The two-stage estimation also involved the estimation of the influence of capital-to-asset ratio on the reciprocal of efficiency scores, and contrary to the expectations, the relationship was found to be positive.